AN EXPERIMENTAL STUDY OF THE EFFECT OF VARIATION OF IMPACT LEVELS ON WORKING EFFICIENCY OF ARCHIMEDES SCREW TURBINE ON MICRO-HYDRO POWER PLANT - Nugraha, Andy; Silalahi, Dani Surya Hamonangan; Ansyah, Pathur Razi; Ramadhan, Muhammad Nizar; Amrullah, Apip; Cahyono, Gunawan Rudi (International Journal of Mechanical Engineering Technologies and Applications, 2023)
Micro-hydro power plants take advantage of the energy potential of low-head airflow. with the development of technology that can support it, namely the Archimedes screw turbine as the driving force. Various parameters must be considered to determine the performance of micro hydro power plants with Archimedes screw turbines. A design is carried out with a discharge parameter flow rate of 2 l/s, a turbine slope of 300, and an immersion level variation of 0.3, 0.5, and 0.7, where the final result shows the value of torque, hydraulic power, mechanical power, generator, and efficiency, which decreases with the level of water immersion in the last blade.